Sex differences in the association between spousal metabolic risk factors with incidence of type 2 diabetes: a longitudinal study of the Iranian population - Azra Ramezankhani; Kamran Guity; Fereidoun Azizi; Farzad Hadaegh (Biology of Sex Differences, 2019)
Abstract Background We investigated whether metabolic risk factors in one spouse were associated with an excessive risk of type 2 diabetes in the other. Methods The study cohort (1999–2018) included 1833 men and 1952 women, aged ≥ 20 years with information on both their own and their spouse’s diabetes status and metabolic risk factors including body mass index (BMI), waist circumference, systolic and diastolic blood pressure, triglyceride to high-density lipoprotein cholesterol ratio, and type 2 diabetes. The associations between spousal metabolic risk factors and type 2 diabetes were estimated using Cox regression models adjusted for the three nested sets of covariates. Results We found 714 (360 men and 354 women) incident cases of type 2 diabetes, after more than 15 years of follow-up. Among women, having a husband with diabetes was associated with a 38% (hazard ratio (HR) 1.38; 95% confidence interval (CI) 1.03, 1. 84) increased risk of type 2 diabetes, adjusted for age, socioeconomic status, individual’s own value of the respective spousal exposure variable, family history of diabetes, and physical activity level. After further adjustment for the woman’s own BMI level, the husband’s diabetes was associated with 23% (HR 1.23; 0.92, 1.64) higher risk of type 2 diabetes in wives, values which did not reach statistical significance. No significant associations were found between spousal metabolic risk factors and incidence of type 2 diabetes among index men. Conclusion We found a sex-specific effect of spousal diabetes on the risk of type 2 diabetes. Having a husband with diabetes increased an individual’s risk of type 2 diabetes. Our results might contribute to the early detection of individuals at high risk of developing type 2 diabetes, particularly, in women adversely affected by their partner’s diabetes.